Upaya Guru Kristen Protestan dan Guru PAI Dalam Mengajarkan Sikap Toleransi Kepada Siswa Yang Berbeda Keyakinan Di SD Negeri 01 Sungai Benai - Asri Karolina; Dwi Hartanti; Peni Nopiyanti; Evi Ismawati; Nur Chasanah (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2023)
Tolerance is very important among students so that they can respect and accept differences, religious tolerance means understanding and respecting the customary beliefs of others. Tolerance is an attitude or human behavior that does not deviate from religious rules, in which a person respects, respects, and provides wide space for followers of religions to embrace their respective religions without any element of coercion from adherents of other religions.This study used a qualitative descriptive research approach using field research. Sources of data obtained came from the Principal of SD Negeri 1 Sungai Benai, Islamic Religious Education Teachers, Non-Muslim Religious Teachers and Homeroom Teachers. Data obtained through interviews, observation, and documentation. While data analysis includes data reduction, data presentation, and drawing conclusions. The results showed that the teacher's efforts to teach religious tolerance at Sungai Benai I Public Elementary School, students at Sungai Benai I Public Elementary School did not question religious differences in interacting and respecting and respecting one another. Teachers at SD Negeri I Sungai Benai are always fair and never discriminate between students. It can be seen from the point of view of the same facilities between Muslims and non-Muslims.